Peripherally tetra-substituted metallophthalocyanines bearing carboxylic acid groups for efficient dye sensitized solar cells - Gorduk, Semih; Altindal, Ahmet (ELSEVIER, 2019)
In this study, carboxylic acid terminated Zn(II), Cu(II), Co(II) and Ni(II) phthalocyanine dyes were synthesized using 3-(4-(3,4-dicyanophenoxy)-3-methoxyphenyl)acrylic acid. Phthalocyanine dyes were characterized by elemental analysis, FT-IR, UV-Vis, H-1-NMR and MALDI-TOF MS techniques. The sensitizing abilities of these dye molecules in standard dye-sensitized solar cells (DSSCs) were also investigated as function of sensitizing time (the sensitizing time was varied from 12 to 72 h). Preliminary studies showed that the sensitization time of TiO2 photoelectrodes has a strong effect on the device performance parameters. Interesting results were obtained for ZnPc sensitized device under optimized conditions. 36 h sensitized ZnPc based device gave a short circuit current density of 18.8 mA cm(-2), an open circuit voltage of 751 mV, a fill factor of 0.46, corresponding to an overall conversion efficiency of 6.37%. Relatively low photovoltaic conversion efficiency for 36 h CoPc sensitized device was obtained which can be attributed to redox active nature of Co(II) metal ion. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Carboxylic acid; Dye; Sensitizer; Solar cell; ZINC PHTHALOCYANINE SENSITIZERS; NANOCRYSTALLINE TIO2 FILMS; MOLECULAR DESIGN; ANCHORING GROUPS; METAL-FREE; PERFORMANCE; CONVERSION; Chemistry